Terapi Islami untuk Mengatasi Kecemasan Akademik Santri: Integrasi Psikologi Klinis dengan Pendekatan Spiritual - Pasaribu, Selamat (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2025)
This research examines the effectiveness of Islamic therapy in addressing academic anxiety among santri (Islamic students) through the integration of clinical psychology with spiritual approaches. Conducted at Pesantren Irsyadul Islamiyah Tanjung Medan, North Labuhanbatu, this qualitative study explores how Islamic therapeutic interventions can complement conventional psychological treatment for academic anxiety. The findings reveal that Islamic therapy, incorporating elements such as dhikr (remembrance of Allah), dua (supplication), Quranic recitation, and spiritual counseling, significantly reduces academic anxiety levels among santri. The integration of clinical psychology principles with Islamic spiritual practices creates a holistic therapeutic approach that addresses both psychological and spiritual dimensions of anxiety. This study contributes to the development of culturally sensitive mental health interventions in Islamic educational settings.